PENANAMAN NILAI-NILAI ISLAMI MELALUI KEGIATAN RUTIN DI PONDOK PESANTREN PUTRI NURUL MUHIBBIN ILUNG - Rahmad Hulbat (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Instilling Islamic values through routine activities for female students is a good thing to do because it can form an Islamic personality. Based on this statement, the focus of the research is the inculcation of Islamic values through routine activities at the Putri Nurul Muhibbin Ilung Islamic Boarding School and the purpose of this study is to find out the inculcation of Islamic values through routine activities at the Putri Nurul Muhibbin Ilung Islamic Boarding School. The type of research used in this research is field research using a qualitative descriptive approach. The data sources for this research are religious teachers, female students, and data related to the issues discussed. Data collection techniques are carried out by means of observation, interviews, and documentation. The data processing uses data reduction, data display, and data verification. Then analyzed using descriptive qualitative method. Based on the results of the research, it is known that the inculcation of Islamic values is through routine activities at the Nurul Muhibbin Ilung Islamic Boarding School which are carried out by female students from Monday to Sunday, namely five daily prayers in congregation, reading istighosah or special wirid, teaching and learning activities of book study, tadarus Al-Qur’an, mudzakarah, mutala’ah, tahlilan, recitation of maulid habsyi, reading of burdah, assembly ta'lim Wednesday afternoon and evening, mutual cooperation, and morning exercises. There are activities that are carried out regularly, especially in instilling Islamic values with the aim of forming Islamic female student habits. Instilling Islamic values through routine activities at the Nurul Muhibbin Ilung Islamic Boarding School includes the values of aqidah, shari’ah values, and moral values as a form of forming Islamic habits and personality of female students based on the Al-Qur’an and As-Sunnah. So that by instilling these Islamic values, especially through routine activities, it is hoped that female students will be able to practice them and increase Islamic potential and shape female students to become human beings who believe and fear Allah SWT and have noble character.